Faith, hope and love - a missionary perspective on three seminal motifs in 1 Thessalonians 1:3 - P. G. R. de Villiers (Acta Theologica)
Paul’s first letter to the Thessalonians is often regarded as providing pastoral support to them in a time of anxiety and stress. Focussing on the introductory part of the thanksgiving in 1 Thessalonians 1:2-5, this article investigates facets of the text that are neglected because of this reading. It analyses certain qualities ascribed to the Thessalonian believers in the first part of the thanksgiving. The qualities are first of all investigated in their general religious sense and, secondly, in terms of their results. In a concluding section the function of this portrait is spelled out.